Evaluating the yield potential of the mutant (M6) short stem Mentik Wangi rice varieties developed through 200-gray gamma irradiation - Himawan, Rifqi; Yunus, Ahmad; Parjanto; Purwanto, Edi (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Mentik Wangi, a traditional aromatic rice variety, faces challenges such as prolonged growth duration and lodging susceptibility, limiting its productivity. The study aimed to evaluate the yield potential and identify high-performing mutant lines of Mentik Wangi rice induced by 200 Gy gamma irradiation. This study addresses the growing need for rice varieties with improved traits to enhance food security in Indonesia. Methods: The research was conducted at the Tegalgondo Rice Seed Garden using a randomized complete block design (RCBD) with three replications. The study included 12 M6 mutant lines of Mentik Wangi rice generated through 200 Gy gamma irradiation. Data were collected on plant growth, yield attributes, and grain quality. Statistical analyses were performed using ANOVA and Duncan's Multiple Range Test to evaluate the significance of observed traits. Findings: The results revealed significant variations among mutant lines for key yield components, including grains per panicle, 100-grain weight, and productivity per hectare. The line M6-MW2-G70-01-14-4-8 demonstrated the highest productivity at 7.29 tons/ha, while all mutant lines exceeded the productivity of the control (3.78 tons/ha). Gamma irradiation was effective in inducing beneficial mutations, enhancing traits such as early maturity, short stems, and higher grain density. Conclusion: The study successfully identified mutant lines of Mentik Wangi rice with improved yield potential and agronomic traits, demonstrating the effectiveness of gamma irradiation as a crop improvement strategy. Novelty/Originality of this article: This research presents innovative findings on the use of gamma irradiation to enhance the productivity and agronomic traits of a traditional rice variety, contributing to the development of high-yielding and locally adapted rice lines.